Beyond individualism: Is there a place for relational autonomy in clinical practice and research? - Dove, ES; Kelly, SE; Lucivero, F; Machirori, M; Dheensa, S; Prainsack, B (SAGE Publications, 2017)
The dominant, individualistic understanding of autonomy that features in clinical practice and research is underpinned by the idea that people are, in their ideal form, independent, self-interested and rational gain-maximising decision-makers. In recent decades, this paradigm has been challenged from various disciplinary and intellectual directions. Proponents of ‘relational autonomy’ in particular have argued that people’s identities, needs, interests – and indeed autonomy – are always also shaped by their relations to others. Yet, despite the pronounced and nuanced critique directed at an individualistic understanding of autonomy, this critique has had very little effect on ethical and legal instruments in clinical practice and research so far. In this article, we use four case studies to explore to what extent, if at all, relational autonomy can provide solutions to ethical and practical problems in clinical practice and research. We conclude that certain forms of relational autonomy can have a tangible and positive impact on clinical practice and research. These solutions leave the ultimate decision to the person most affected, but encourage and facilitate the consideration of this person’s care and responsibility for connected others.